2010
DOI: 10.1002/cncr.25260
|View full text |Cite
|
Sign up to set email alerts
|

Sequential magnetic resonance imaging of cervical cancer

Abstract: BACKGROUND:The objectives of this study were to investigate outcome prediction by measuring absolute tumor volume and regression ratios using serial magnetic resonance imaging (MRI) during radiation therapy (RT) for cervical cancer and to develop algorithms capable of identifying patients at risk of a poor therapeutic outcome. METHODS: Eighty patients with stage IB2 through IVA cervical cancer underwent 4 MRI scans: before RT (MRI1), during RT at 2 to 2.5 weeks (MRI2) at 4 to 5 weeks (MRI3), and 1 to 2 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…Tumor volume changes after therapy have shown to be associated with survival in different solid tumors, including locally-advanced rectal adenocarcinoma treated with chemoradiotherapy and surgery [42], cervical cancer receiving radiotherapy [43], and malignant pleural mesothelioma treated with chemotherapy, extrapleural pneumonectomy, and radiation [44]. In lung cancer, Zhao et al reported that semiautomated tumor segmentation identified a larger number of patients with absolute tumor volume changes, compared with unidimensional or bidimensional techniques [23].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor volume changes after therapy have shown to be associated with survival in different solid tumors, including locally-advanced rectal adenocarcinoma treated with chemoradiotherapy and surgery [42], cervical cancer receiving radiotherapy [43], and malignant pleural mesothelioma treated with chemotherapy, extrapleural pneumonectomy, and radiation [44]. In lung cancer, Zhao et al reported that semiautomated tumor segmentation identified a larger number of patients with absolute tumor volume changes, compared with unidimensional or bidimensional techniques [23].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment response can be assessed as early as during the course of radiation therapy by measurement of initial tumor volume and tumor regression rate (22, 28-30). The tumor volumes were measured by using T2-weighted MR images and the initial tumor volumes estimated from the first MRI scans were significantly correlated with treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…1). The regression demonstrated by MRI after 45 Gy EBRT compared to the baseline MRI has been shown to be a potentially significant predictor of local recurrence (15). 3D imaging, particularly with MRI, provides a significant benefit to ensure dosimetric coverage of the tumor and avoidance of the nearby OAR (vagina, bladder, rectum, sigmoid, and bowel) (Fig.…”
Section: Clinical Approachmentioning
confidence: 99%